Mendidik Anak ADHD Perspektif Orang Tua Dan Guru Dalam Meningkatkan Prestasi Akademik - Adelia Putri; Abd Rosyid (STAI Al Mujtama Pamekasan, 2025)
This study aims to analyze the management of children with attention Deficit Hyperaktivity Disorder (ADHD) at Al-maqbul kindergarten (TKS), as well as the roles of teachers and parents in proving the academic achievement of children with ADHD. This study used a qualitative approach with case studies, through data collection from observations, interviews, and documentation. The results indicate that children with ADHD exhibit hyperactive behavior that requires special treatment in the form of stimulation, motivation, and assignments appropriate to their abilities. Teachers play a crucial role as facilitators and motivators, providing emotional support through praise and educational activities, while parents serve as the primary environment supporting children’s learning at home. Collaboration between parents and teachers through regular communication and integrated strategies has been shown to improve the academic achievement of children with ADHD. The research findings emphasize the importance of an integrated approach between schools and families in managing children with ADHD to ensure optimal growth and development appropriate to their age.